Stepping Toward Self‐Powered Papertronics: Integrating Biobatteries into a Single Sheet of Paper. Issue 1 (18th October 2016) - Gao, Yang; Choi, Seokheun
Abstract : A stackable and 3D manufactured bacteria‐powered battery is constructed within a single sheet of paper for on‐chip, disposable paper‐based electronics or "papertronics." The manufacturing technique on paper greatly reduces fabrication time and cost of the biobatteries and revolutionizes their potential use as a disposable power source in remote and resource‐limited regions for self‐powered papertronics.